Identification of genetic determinants of tomato brown rugose fruit virus that enable infection of plants harbouring the Tm‐22 resistance gene. (13th August 2021) - Yan, Zhi‐Yong; Ma, Hua‐Yu; Wang, Lu; Tettey, Carlos; Zhao, Mei‐Sheng; Geng, Chao; Tian, Yan‐Ping; Li, Xiang‐Dong
Abstract: Tomato cultivars containing the Tm‐2 2 resistance gene have been widely known to resist tobacco mosaic virus (TMV) and tomato mosaic virus. Tomato brown rugose fruit virus (ToBRFV), a new emerging tobamovirus, can infect tomato plants carrying the Tm‐2 2 gene. However, the virulence determinant of ToBRFV that overcomes the resistance conferred by the Tm‐2 2 gene remains unclear. In this study, we substituted the movement protein (MP) encoding sequences between ToBRFV and TMV infectious clones and conducted infectivity assays. The results showed that MP was the virulence determinant for ToBRFV to infect Tm‐2 2 transgenic Nicotiana benthamiana plants and Tm‐2 2 ‐carrying tomato plants. A TMV MP chimera with amino acid residues 60–186 of ToBRFV MP failed to induce hypersensitive cell death in the leaves of Tm‐2 2 transgenic N. benthamiana plants. Chimeric TMV containing residues 60–186 of ToBRFV MP could, but chimeric ToBRFV containing 61–187 residues of TMV MP failed to infect Tm‐2 2 transgenic N. benthamiana plants, indicating that 60–186 residues of MP were important for ToBRFV to overcome Tm‐2 2 gene‐mediated resistance. Further analysis showed that six amino acid residues, H 67, N 125, K 129, A 134, I 147, and I 168 of ToBRFV MP, were critical in overcoming Tm‐2 2 ‐mediated resistance in transgenic N. benthamiana plants and tomato plants. These results increase our understanding of the mechanism by which ToBRFV overcomes Tm‐2 2 ‐mediated resistance. Abstract : Six amino acid residues, H 67, N 125, K 129, A 134, I 147, and I 168, located in the central region of the movement protein are involved in tomato brown rugose fruit virus to evade Tm‐2 2 ‐mediated resistance.